An unusual presentation of ossified spinal meningioma: case report and literature review - Xu, Wen-Bin; Sun, Nai-Kun; Cai, Di-Xin; Chen, Ding-Qiang; Niu, Yuan; Jia, Fang; Lin, Guang-Xun; Rui, Gang (Frontiers in Oncology, 2023)
Background: Spinal meningioma is a common intraspinal tumor, which mainly occurs in the thoracic spine. Ossified meningioma (OSM) is an extremely rare histological variant. Our article reports a rare patient with dorsal complete OSM and reviews this subject. Case Presentation: A 68-year-old woman presented with a one-year history of progressive weakness in both lower limbs with gait disturbance. Physical examination revealed hypoesthesia with a sensory level below T10. Babinski and pathological signs on both sides were weakly positive. Magnetic resonance imaging (MRI) showed a mass at the T10 to T11 level causing severe compression of the spinal cord. Computed tomography (CT) showed complete ossification of the mass. 18F-Fluoro-deoxy-glucose positron emission tomography CT (18F-FDG PET/CT) scan combined with MRI revealed that the mass was an intradural extramedullary high-density ossified nodule. The patient underwent a gross total resection of the mass and pathologic examination indicated that the mass was a meningioma with diffused psammomatous bodies. Conclusion: We identified a rare case of dorsal complete OSM occurring in a 68-year-old woman. After complete surgical resection, although there were complications such as cerebral fluid leakage and fever, the patient finally recovered with a satisfactory result.